The holiday switch - Marcelo, Tif (New York : Underlined, 2021)
Planning to enjoy her last snowy winter break of high school by working at a cozy local inn and moonlighting as an anonymous book blogger, Lily Santos' plans are upended when the boss's frustratingly cute nephew, Teddy Rivera, becomes her nemesis co-worker ... then the two accidentally switch phones, a snafu that may just reveal their secrets and bring the rivals together.
HL670L
Keywords: Teenagers -- Fiction; Man-woman relationships -- Fiction; Bloggers -- Fiction; Young adult fiction